Numerical modeling of fusiform aneurysm with high and normal blood pressure - Badreddin, Giuma S. K. (Institute of Electrical and Electronics Engineers, 2009)
Fusiform shape of aneurysm is a common geometry of Abdominal Aorta Aneurysm (AAA). One of the ways to detect the presence of fusiform aneurysm is by performing computer tomography scan of the body. In this study, actual output of the CT-Scan was converted to 3D model in numerical modeling. The objective of this work is to study the effect of hypertensive blood pressure and the wall shear stress (WSS) since hypertension is reported to be a risk factor in rupture of fusiform aneurysms. The numerical prediction shows that the transient behavior of the interaction under hypertensive blood pressure is significantly different from that under normal blood pressure. The peak wall stress, peak WSS and peak deformation occur shortly after systolic peak pressure. The location of maximum WSS is not where the pressure is the highest but rather where the pressure gradient is the largest.